The first observation and data reduction of the Multi-wavelength Spectrometer on the New Vacuum Solar Telescope - Wang, Rui; Xu, Zhi; Jin, Zhen-Yu; Li, Zhi; Fu, Yu; Liu, Zhong (Research in astronomy and astrophysics, 2013)
The Multi-wavelength Spectrometer is a medium-dispersion（R~130 000）grating spectrometer installed on the New Vacuum Solar Telescope at the Fuxian Solar Observatory,Yunnan Astronomical Observatory,Chinese Academy of Sciences.It is designed to accurately observe the velocity and magnetic fields of the Sun.The present configuration of this spectrometer allows us to simultaneously observe three different solar spectral lines.This work is dedicated to showing the first observations carried out in both the Hαand Ca II 8542 A lines.We give a detailed description of the data reduction process,focusing on the retrieval of a flat field from the high-resolution spectral data.Two different methods are also performed and compared to eliminate the residual fringe in the reduced data.The real spectral resolution and instrumental profile are analyzed based on the final results,which indicate that this spectrometer presently satisfies the expected performance and it is ready for further scientific observations.